Lithium disilicate glass-ceramic surface analysis by atomic force microscopy and optical microscopy - Brondino, Bárbara Margarido (2018)
Objective: The primary objective of this study was to evaluate the roughness of CAD/CAM blocks of lithium disilicate glass-ceramic (IPS e.max CAD, Ivoclar Vivadent®, Schaan, Liechtenstein), before and after surface treatment with hydrofluoridric acid 10% and after silane coating by Atomic Force Microscopy and Optical Microscopy. The average size of silane as well as its fit to the valleys after acid etching was also studied. Methods: Ten specimens of CAD/CAM blocks of lithium disilicate glass-ceramic were analyzed by Atomic Force Microscopy. Before surface treatment with hydrofluoridric acid 10%, the specimens were also analyzed by Atomic Force Microscopy. All specimens were also analyzed by Optical Microscopy after the application of a layer of silane. Free software Gwyddion version 2.51 was used on data processing. The 3D surface measurements were: root mean square roughness, average roughness, maximum peak height, maximum pit depth, maximum height, Skewness and Kurtosis of surface and profile roughnesses. Images provided by Optical Microscopy were used to calculate the size of the silane particle, also using the free software Gwyddion version 2.5.1. Non-parametric tests were done by the free software R version 3.5.1. Results: Surface roughness and profile roughness were numerically different, but both increased after acid etching. All the skewness measurements concentrated around zero, indicating a more symmetrical behavior after acid conditioning. Silane cross-sectional area measured from 0,0374m² to 0,424351m² and its radius ranged from 0,115m to 0,3675m and could fit in on about 77,5% of the conditioned surface valleys. Significance: Roughness surface and silane layer are important factors to the bond strength between ceramic and resin cements, ensuring the success of restorative treatment.